Pumpkin heads! - Minor, Wendell (New York : Blue Sky Press, 2000)
Pumpkin heads and jack-o-lanterns of all varieties abound when Halloween comes around.
School Library Journal.
Pub Weekly.
Booklist.
1.0
K-3
Keywords: Pumpkin -- Fiction; Halloween -- Fiction; Jack-o-lanterns -- Fiction; Pumpkins -- Fiction; Halloween -- Fiction; Jack-o-lanterns -- Fiction; Pumpkin -- Fiction; Halloween -- Fiction; Jack-o-lanterns -- Fiction